2013
DOI: 10.1176/appi.ajp.2012.12070971
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Functional Remediation in Bipolar Disorder: A Multicenter Randomized Controlled Study

Abstract: OBJECTIVE The authors sought to assess the efficacy of functional remediation, a novel intervention program, on functional improvement in a sample of euthymic patients with bipolar disorder. METHOD In a multicenter, randomized, rater-blind clinical trial involving 239 outpatients with DSM-IV bipolar disorder, functional remediation (N=77) was compared with psychoeducation (N=82) and treatment as usual (N=80) over 21 weeks. Pharmacological treatment was kept stable in all three groups. The primary outcome measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
216
4
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 281 publications
(240 citation statements)
references
References 26 publications
12
216
4
8
Order By: Relevance
“…One intervention, functional remediation (FR), involves a 21‐session group intervention over 6 months. In a large RCT, FR was shown to have a substantial impact on functioning, in comparison to treatment as usual 117. Coupled with the results of other small studies involving other interventions, these findings suggest that there is considerable hope in addressing cognitive and functional deficits in BD 118.…”
Section: Foundations Of Managementmentioning
confidence: 59%
“…One intervention, functional remediation (FR), involves a 21‐session group intervention over 6 months. In a large RCT, FR was shown to have a substantial impact on functioning, in comparison to treatment as usual 117. Coupled with the results of other small studies involving other interventions, these findings suggest that there is considerable hope in addressing cognitive and functional deficits in BD 118.…”
Section: Foundations Of Managementmentioning
confidence: 59%
“…Deckersbach et al 17 reported five dropouts from 18 participants and Preiss et al 18 reported 21 dropouts out of 45 participants at study outset. Torrent et al 20 reported that 28.6% patients discontinued in the functional remediation group, 24.4% discontinued rehabilitation in BD are more likely to be published.…”
Section: Discussionmentioning
confidence: 99%
“…19 Unfortunately, the authors did not report the number of sessions per week or the CR procedures employed. The article published by Torrent et al 20 was an exception, describing the main topics of each session. We suggest that future studies should clearly describe their samples and intervention procedures with a view to enabling replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a study showed that while almost all patients with first-episode mania had recovery from the syndrome within 2 years, only one-third of them achieved functional recovery [19]. A functional remediation therapy was recently developed in order to address this functional impairment [20]. A multicenter randomized controlled trial with 239 outpatients with bipolar disorder showed that functional remediation presented significant efficacy in improving functional impairment as compared with treatment as usual for euthymic patients over 21 weeks of treatment [20].…”
Section: Functioning and Neurocognitive Impairmentmentioning
confidence: 99%